Analisis Risiko Keamanan dan Keselamatan Penumpang Kapal Perintis di Pelabuhan Sorong: Pendekatan Systemic Accident Model dan Swiss Cheese Theory - Haryanto, Dwi; Setiyono, Muji; Nashrul, Arief; Huda, Robitthotul (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze passenger safety and security risks of pioneer ships operating at Sorong Port using a systemic perspective based on the Systemic Accident Model. A qualitative descriptive approach was employed. The findings indicate that maritime safety risks are shaped by the interaction of three main factors: technical factors, including limited vessel seaworthiness and predominantly reactive maintenance practices; human factors, characterized by high workload, crew fatigue, and weak safety culture; and environmental factors, such as dynamic sea conditions and insufficient navigational aids at the port. These results demonstrate that the safety management of pioneer vessels at Sorong Port has not yet been optimally implemented. Therefore, enhancing maritime safety requires an integrated safety management system that encompasses fleet modernization, improvement of crew competence and safety awareness, and strengthening port infrastructure and safety oversight.